Kajian Ruang Kepegawaian Di Gedung Komisi Nasional Disabilitas dalam Konsep Desain Inklusif - Harahap, Rachmita Maun; Permatasari, Chandrarezky; Hayati, Arina; Bararatin, Kirami (INKLUSI, 2022)
The purpose of the study is to identify the design aspects of working environment based on the experience of people with disability. The first floor of Komisi Nasional Disabilitas (KND) workspace which used by National Commission for Disabilities as its secretariat, will be the priority case of this study. The study examine how to implement the inclusive design concept in the workplace focus on realizing equal opportunities in the implementation of Respect, Protection and Fulfillment of the Rights of Persons with Disabilities. The research use qualitative approach, include the use of methods such as in-depth interviews, participant observation, architectural and interior elements’ measurement based on Universal Design and Deaf Space principles. Quantitative approach is also applied by using questioners’ assessment for measuring values of environment by way of comparison with the regulations of Universal Design and Deaf Space guidelines. The results shows that personal experience of people with disability plays important role to evaluate their environment. The meaning of inclusive and accessible environment can be vary based on the participants’ interpretation. Yet during the participant observation, the study reveals that the building and interior spaces of KND have not been designed to meet the principles of universal design and deaf space. The participants mostly have done some physical adjustment and spatial/furniture arrangements to meet their personal conditions, needs, and preference to carry out their daily activities independently. In conclusion, this research proposes design parameters from the perspective of the participants elaborated with the principles Universal design and Deaf Space in effort to increase inclusivity for all users.